Adaptation to water-induced disaster: exploring local knowledge and Indigenous knowledge-led strategies - Rittelmeyer, Pamela; Caretta, Martina Angela; Dowler, Calynn; Vora, Shuchi; Seigerman, Cydney K.; Reddy, EB Uday Bhaskar; BR, Lakshmikantha; Parajuli, Jagadish; Srinivasan, Jaishri; Priya, Ritu; Mukherji, Aditi (SAGE Publications, 2024)
The magnitude of water-induced disasters is projected to increase in the coming decades. Yet, there is a substantial gap in the understanding of how local knowledge and Indigenous knowledge are employed to respond to climate change water-induced disasters. We examine this gap through a meta-review of literature published between 2014 and 2019 yielding 39 scholarly papers. The meta-review indicates that the literature highlights that marginalized people are facing multiple risks that threaten their ability to produce enough food for consumption, secure water for irrigation, live in sustainable communities, and maintain their health and well-being. Responses are largely incremental, autonomous adjustments, such as livelihood diversification, flood-proofing homes, and soil moisture conservation. Our findings show that there is a clear need to more closely attend to the processes by which local knowledge and Indigenous knowledge can be meaningfully integrated into adaptation to move toward transformative change for long-term climate resilience.